Instagram photo sharing and its relationships with social rewards and well‐being. Issue 3 (13th July 2020) - Maclean, Julie; Al‐Saggaf, Yeslam; Hogg, Rachel
Abstract: Photo sharing is one of the most popular online activities and prior research has revealed conflicting findings regarding its relationships with well‐being. While a number of studies have found sharing photos improves well‐being, other studies have found that photo sharing actually worsens well‐being. This research examined the relationship between well‐being and social rewards generated from sharing different types of photos on the most used online photo sharing platform, Instagram. Our research focused on the active sharing of photos on Instagram rather than the passive consumption of photos, so the relationship with well‐being could be better understood. Our research also differentiated between sharing photos of oneself and other photos and investigated the difference between positive and negative social rewards to understand their relationships with well‐being. These aspects have not been previously explored. Results from an online survey of 373 participants found that online social rewards of likes and positive comments was correlated with well‐being. Well‐being was significantly correlated with sharing photos of oneself as compared with other types of photos. Social rewards satisfaction was significantly correlated with well‐being and was found to be a predictor of well‐being, which suggests satisfaction of online interactions is associated with well‐being. One obvious implication for social media design and policy would be to provide additional facilities for allowing ease of sharing photos that maximize social rewards and satisfaction levels. Social media providers could enable users to monitor their well‐being levels to maximize their satisfaction with social rewards so as to improve their well‐being levels.